Artificial Intelligence in Process Automation for Competitive Strategy in Logistics: RSL - Zaga Palomino, Cielo Aheli; Chire Vilcarima, Ansferny Keith (LACCEI, 2025)
The primary goal of this study work will focus on carrying out a complete analysis on how the implementation of AI and the incorporation of automation allow not only the improvement in business processes, but also the strengthening and continuous optimization of competitive strategies, which will be key during the process of creating this study's systematic review. The methodology used involves an in- depth analysis of scientific studies from the "Scopus" database. Fifty-five of the 172 pertinent papers that were found were chosen for this review, utilizing strict inclusion and exclusion standards, as well as full-text access. The analysis of the following study has three main characteristics where it is evidenced: [1] The automation and use of AI to business process optimization. [2] The identification of tools and applications that contribute significantly to strategic decision-making and improving operational productivity. [8] For business competitiveness, these technologies are used, which have a great impact on both advantages and ethical and technical challenges. It is evident that automation in business processes together with AI favors operational efficiency, maximizing resources and improving capacity for market adaptation.Furthermore, it is evident that corporate accountability must be upheld when utilizing these technologies. This evaluation will be beneficial for new and future research on process optimization using automation and artificial intelligence, and will allow business managers to offer fundamental strategies. The aim is to ensure that the results obtained offer a greater understanding of these technologies and are applicable in the workplace.